IBM Center for Cloud Training Helps Close the Cloud Talent Gap - Brooks Powell, Natalie (International Journal of Advanced Corporate Learning (iJAC), 2024)
With technology becoming increasingly critical to business success, the value of training is becoming more apparent. As a result, learning and development (L&D) is playing a larger role in the success of professionals and the corporations that employ them. For the IBM Center for Cloud Training (ICCT), the challenge was clear: to close the gap between the numbers of people needed to manage the growing field of Cloud technology and the numbers of people qualified for those jobs. The opportunity and path to success also were clear: ICCT provides its clients with innovative learning programs and award-winning support. ICCT’s efforts have played a significant role in building a worldwide body of qualified professionals trained in the role-based and technical skills necessary to enable one of the fastest growing aspects of computer technology.